2020
DOI: 10.1093/rheumatology/keaa509
|View full text |Cite
|
Sign up to set email alerts
|

Anti-protein C antibodies and acquired protein C resistance in SLE: novel markers for thromboembolic events and disease activity?

Abstract: Objectives Risk factors for thromboembolism in SLE are poorly understood. We hypothesized a possible role for protein C, based on its dual activity in inflammation and haemostasis and on the evidence of an association between acquired activated protein C (APC) resistance (APCR) and high-avidity anti-protein C antibodies (anti-PC) with a severe thrombotic phenotype in venous thrombosis APS patients. Methods In a cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 51 publications
(66 reference statements)
0
27
0
Order By: Relevance
“…A case of SLE presenting with positive APL, acquired APCR and autoimmune hemolytic anemia was reported[ 19 ]. However, in the study by Ramirez et al [ 20 ], anti-PC was associated with APCR in patients with SLE, independently of APL. Studies showed an association between reduced PS levels and APL in patients with SLE[ 21 , 22 ]; however, another study found no association between decreased PS levels and ACL[ 23 ].…”
Section: Discussionmentioning
confidence: 91%
“…A case of SLE presenting with positive APL, acquired APCR and autoimmune hemolytic anemia was reported[ 19 ]. However, in the study by Ramirez et al [ 20 ], anti-PC was associated with APCR in patients with SLE, independently of APL. Studies showed an association between reduced PS levels and APL in patients with SLE[ 21 , 22 ]; however, another study found no association between decreased PS levels and ACL[ 23 ].…”
Section: Discussionmentioning
confidence: 91%
“…More recently, we also expanded on this work using both Protac ® and exogenous APC. APCr was observed in SLE independently of aPL positivity, while patients with thrombosis tended to exhibit APCr to both reagents [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seventy-five healthy normal controls were also recruited and used to establish cut off values for the assays. APCr with the CAT system was previously reported for 30 thrombotic APS, 20 non-thrombotic controls [ 9 ] and for 53 SLE patients [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations